Overview of The Results of Tuberculosis (TB) Examination with Molecular Rapid Test (TCM) at X Hospital in Gamping Regency, 2023-2024 - Selna Hamidjun; Farida Noor Irfani; Nazula Rahma Shafriani (Rifa'Institute, 2026)
Introduction: Tuberculosis (TB) is a significant global health problem, including in Indonesia. In the Special Region of Yogyakarta, TB prevalence is quite high, with a higher incidence among men than women. The Molecular Rapid Test (TCM) method using the GeneXpert MTB/RIF machine has been recommended by the World Health Organization as a fast and accurate diagnostic tool to detect the presence of Mycobacterium tuberculosis as well as resistance to rifampicin. Objective: This study aims to describe the results of TCM examinations in TB patients at X Gamping Hospital during the period 2023-2024 and to analyze the influence of age and gender on the examination result. Method: The study used a cross-sectional retrospective design with secondary data collection from the medical records of patients undergoing GeneXpert TCM examination. Result and Discussion: The results showed that the majority of patients were in the productive age group (15-64 years) as much as 74.1% and dominated by men at 58.9%. All patients showed Rifampicin Sensitive results. Conclusion: Most tuberculosis patients at X Gamping Hospital in 2023-2024 were of productive age (15-64 years) and were mostly male